Konsep Bimbingan Agama Islam terhadap Wanita Tuna Susila di UPT Rehabilitasi Sosial Tuna Susila Kediri - Dafid Fajar Hidayat (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2017)
This research was conducted to deeply examine the concept of Islamic religious guidance that has been done by UPT Rehabilitation of Social Tuna Susila Kediri against prostitute women, with the concept of guidance of Islamic religion is done carefully to equip clients to have knowledge about Islam and be able to apply it. So that eventually the client can return to the right path in accordance with the teachings of Islam and the guidance of Rasulullah SAW